2006
DOI: 10.1097/01.aog.0000245784.31082.ed
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Prolapse in Nulliparous Women and Their Parous Sisters

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…It is nowadays widely accepted that underlying connective abnormalities, as well as hereditary factors, predispose to POP, and our study shows that they also predispose to POP recurrence [20][21][22][23].…”
Section: Discussionsupporting
confidence: 57%
“…It is nowadays widely accepted that underlying connective abnormalities, as well as hereditary factors, predispose to POP, and our study shows that they also predispose to POP recurrence [20][21][22][23].…”
Section: Discussionsupporting
confidence: 57%
“…However, also nulliparous women without any risk factors may develop POP. Therefore, a genetic predisposition may play a role as well [6][7][8]. When a mother has POP, the relative risk for the daughter of developing POP is 3.2.…”
Section: Introductionmentioning
confidence: 99%
“…It is nowadays widely accepted that underlying connective abnormalities, (in addition to hereditary factors), predispose to POP, and our study shows that they also predispose to POP recurrence [20][21][22][23]. Nevertheless, we found that POP severity, expressed most distal preoperative POP stage, was associated with a significantly greater blood loss, and higher incidence rates of perioperative and long-term complications.…”
Section: Discussionmentioning
confidence: 44%